Prospecção química da macroalga marinha verde Ulva fasciata Delile - Alencar, Daniel Barroso de (2010)
Marine macroalgae have been considered promising sources of bioactive compounds. These compounds exhibit different biological properties, such as antibacterial, antifungal, antiviral, anti-inflammatory, antihelminthic, antileshmaniose, antimalaria, antioxidants, and antitumor. Their use as medicine has spurred the interest of many researches. The objective of this work was to carry out a phytochemistry investigation of the ethanolic extract of green marine macroalga Ulva fasciata. The plant material was collected in April 2008 at Pacheco Beach, Caucaia-CE. Macroalgae in natura were dehydrated in an air-circulation oven at 40°C for 15 hours. After the drying process, the material was cut into small pieces. 500 grams were submitted to a cold extraction with hexane (UFH) followed by an extraction with 70% ethanol (UFE). Both isolation and purification from fixed constituents were performed using a combination of classic chromatographic techniques. Three samples were isolated and named UF-1, UF-2 and UF-3. The presence of a major constituent (86.17%) with retention time of 24.940 min was observed in the first sample (UF-1), and its mass spectrum was characterized by the molecular ion M+ 284. The GC-MS analysis suggestion and the comparison of its spectrum with literature reinforce its identification as ethyl hexadecanoate with a similarity index of 96%. Compounds UF-2 and UF-3 have been taken to the Northeastern Center of Application and Use of Nuclear Magnetic Resonance (CENAUREMN) of Federal University of Ceara, to determine the chemical structure by spectroscopy techniques such as uni- and bidimensional (1H, 1H-COSY, gs-HMQC, gs-HMBC, ROESY, NOESY and TOCSY) 1H-NMR and 13C-NMR, as well as mass spectrometry (MS).